Anti-reflection substrate
The anti-reflective substrate achieves low visual reflectivity and anti-fouling properties by using a combination of substrate, hard coat, light absorbing, and low refractive index layers, eliminating the need for additional anti-fouling coatings and reducing production complexity and costs.
Patent Information
- Application Number
- JP2022532464
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-17
- Filing Date
- 2021-05-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-05-31
AI Technical Summary
Existing anti-reflective substrates require multiple layers and complex processes to achieve low visual reflectivity and anti-fouling properties, making them expensive and time-consuming to produce.
A substrate configuration involving a substrate layer, hard coat layer, light absorbing layer, and a low refractive index layer made from a cured resin composition containing hollow silica and a fluorine-based compound, which is cured using active energy rays, achieving anti-reflective properties without the need for additional anti-fouling layers.
This configuration effectively reduces visual reflectivity to 1.0% or less and imparts anti-fouling properties without the need for additional coatings, improving productivity and reducing costs.
Smart Images

Figure 0007658372000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an antireflective substrate, and in particular to an antireflective substrate having low luminous reflectance and excellent antifouling properties. [Background technology]
[0002] In display applications such as smartphones, car navigation systems, and game consoles, materials with anti-reflective properties are used to prevent reflections of external light.
[0003] Anti-reflection materials generally use optical interference technology. Optical interference generally uses optical thin films with a thickness thinner than the wavelength of visible light. In particular, to achieve ultra-low reflection with a luminous reflectance of 1.0% or less, it is necessary to coat the optical thin films in multiple layers. For example, an anti-reflection film with a four-layer structure such as Nb2O5-SiO2-Nb2O5-SiO2 on an adhesive layer is known (Patent Documents 1 and 2). However, forming such a multi-layer film requires a large number of film-forming devices, which results in high costs, which is an issue. In addition, anti-soiling function is required for use in displays, so an anti-soiling layer must be installed on the outermost layer.
[0004] On the other hand, a method of using a light absorbing layer is known as a method of lowering the luminous reflectance while reducing the number of layers (Patent Documents 3 and 4). Titanium nitride, zirconium nitride, gold, silver, copper, etc. can be used as the light absorbing layer, and it is preferable to use one in which the refractive index n has a negative wavelength dispersion and the extinction coefficient k has a positive wavelength dispersion. By forming a film with a low refractive index such as SiO2 on these light absorbing layers, it is possible to achieve a low luminous reflectance even with a two-layer coating. However, even with this method, an anti-soiling function is required for use in a display, so an anti-soiling layer must be provided on the outermost layer.
[0005] As a method for forming an antifouling layer on a light absorbing layer, a method of coating the light absorbing layer with organic silane and fluorine is known (Patent Document 5). This method is thermal curing, and has low productivity, and the problem is that it requires long-term heating to achieve stable physical properties.
[0006] To improve anti-reflection performance, it is desirable for the low refractive index layer to have a low refractive index. However, the refractive index of SiO2, a commonly used material, is high at 1.46, making it difficult to achieve sufficient anti-reflection performance. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent Publication No. 2019-35969 [Patent Document 2] Patent Publication No. 2018-8431 [Patent Document 3] Patent Publication No. 10-96801 [Patent Document 4] Patent Publication No. 9-73001 [Patent Document 5] Patent Publication No. 2002-341107 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0008] An object of the present invention is to provide an antireflection substrate that realizes low luminous reflectance and antifouling properties with fewer steps and fewer layers. [Means for solving the problem]
[0009] As a result of intensive research into solving the above problems, the inventors of the present invention have found that the above problems can be solved by the following invention. That is, the present invention is as follows. <1> An anti-reflection substrate comprising the following layers (A), (B), (C) and (D) laminated in this order: (A) Base material layer (B) Hard coat layer (C) Light absorbing layer (D) A low refractive index layer obtained by curing a low refractive index resin composition containing an active energy ray curable resin, hollow silica, and a fluorine-based compound with active energy rays. The antireflection substrate as described above, wherein the light absorbing layer (C) has a thickness of 1 to 20 nm. <2> The (C) light absorbing layer is formed from at least one selected from the group consisting of titanium nitride, titanium oxynitride, zirconium nitride, gold, silver, and copper. <1> The anti-reflection substrate according to claim 1, <3> The (C) light absorbing layer has a thickness of 2 to 15 nm. <1> or <2> The anti-reflection substrate according to claim 1, <4> The active energy ray curable resin in the (D) low refractive index layer contains a urethane (meth)acrylate component. <1> from <3> The antireflection substrate according to any one of claims 1 to 5, <5> The above, wherein the fluorine-based compound in the (D) low refractive index layer has a perfluoropolyether bond. <1> from <4> The antireflection substrate according to any one of claims 1 to 5, <6> The (D) low refractive index layer has a refractive index of 1.45 or less at a wavelength of 550 nm. <1> from <5> The antireflection substrate according to any one of claims 1 to 5, <7> The visual reflectance is 1.0% or less. <1> from <6> The antireflection substrate according to any one of claims 1 to 5, <8> The above does not include an antifouling layer. <1> from <7> The antireflection substrate according to any one of claims 1 to 5, Effect of the Invention
[0010] By using the method of the present invention, it is possible to produce an anti-reflection substrate having anti-soiling properties without applying an additional anti-soiling coating. The anti-reflection substrate of the present invention has the advantage of having a low luminous reflectance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, the present invention will be described in detail by way of examples and working examples. However, the present invention is not limited to the illustrated examples and working examples, and can be modified in any manner without departing from the scope of the present invention.
[0012] [Base material layer] In the present invention, the material constituting the substrate layer is not particularly limited, but a glass substrate, a metal substrate, or a plastic substrate can be used. In particular, plastic substrates have a wide variety of compounds constituting them and are used in various fields.
[0013] The plastic substrate preferably contains a thermoplastic resin. The type of thermoplastic resin is not particularly limited, but examples thereof include polycarbonate (PC) resin, acrylic resin such as polymethyl methacrylate (PMMA), polyethylene terephthalate (PET), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyimide (PI), cycloolefin copolymer (COC), norbornene-containing resin, polyethersulfone, cellophane, and aromatic polyamide.
[0014] The polycarbonate resin contained in the base layer is not particularly limited as long as it contains a -[OR-OCO]- unit (wherein R contains an aliphatic group, an aromatic group, or both an aliphatic group and an aromatic group, and further has a straight-chain structure or a branched structure) containing a carbonate bond in the molecular main chain, but is preferably a polycarbonate having a bisphenol skeleton, and is particularly preferably a polycarbonate having a bisphenol A skeleton or a bisphenol C skeleton. As the polycarbonate resin, a mixture or copolymer of bisphenol A and bisphenol C may be used. By using a bisphenol C-based polycarbonate resin, for example, a polycarbonate resin containing only bisphenol C, or a mixture or copolymer of bisphenol C and bisphenol A, the hardness of the base layer can be improved. The viscosity average molecular weight of the polycarbonate resin is preferably from 15,000 to 40,000, more preferably from 20,000 to 35,000, and further preferably from 22,500 to 25,000.
[0015] The acrylic resin contained in the base layer is not particularly limited, but may be, for example, a homopolymer of various (meth)acrylic acid esters such as polymethyl methacrylate (PMMA) or methyl methacrylate (MMA), or a copolymer of PMMA or MMA with one or more other monomers, or a mixture of a plurality of these resins. Among these, a (meth)acrylate containing a cyclic alkyl structure having low birefringence, low moisture absorption, and excellent heat resistance is preferred. Examples of such (meth)acrylic resin products include, but are not limited to, Acrypet (manufactured by Mitsubishi Rayon), Delpet (manufactured by Asahi Kasei Chemicals), and Parapet (manufactured by Kuraray).
[0016] It is also possible to use a two-layered product containing a polycarbonate resin and the above-mentioned acrylic resin. By using a two-layered product containing a polycarbonate resin and the above-mentioned acrylic resin, it is possible to improve the surface hardness while maintaining the thermoformability of the base layer.
[0017] The substrate layer may also contain additives as components other than the thermoplastic resin. For example, at least one additive selected from the group consisting of a heat stabilizer, an antioxidant, a flame retardant, a flame retardant assistant, an ultraviolet absorber, a release agent, and a colorant. In addition, an antistatic agent, a fluorescent brightener, an antifogging agent, a flow improver, a plasticizer, a dispersant, an antibacterial agent, etc. may be added to the substrate layer.
[0018] [Hard coat layer] In the present invention, a hard coat layer is provided on the substrate layer. For example, it is possible to use a hard coat applied to the thermoplastic resin constituting the substrate layer. The hard coat layer can be formed by applying a hard coat composition containing an active energy ray curable resin, drying the composition, and then curing the composition with active energy rays, or by applying a thermosetting compound, drying the composition, and then heating the composition to cure the composition. Among these, it is preferable to apply a hard coat composition containing an active energy ray curable resin, drying the composition, and then curing the composition with active energy rays.
[0019] The active energy ray curable resin can be any compound having a functional group having active energy ray curability, but preferably contains a urethane (meth)acrylate component. The urethane (meth)acrylate contains a polymer of a resin material containing a urethane (meth)acrylate derived from a polyol, an isocyanate, and a (meth)acrylate, and a (meth)acrylate. That is, it is preferable that the active energy ray curable resin is a mixture of a urethane (meth)acrylate obtained by a dehydration condensation reaction of the three components of a polyol, an isocyanate, and a (meth)acrylate, and a (meth)acrylate.
[0020] Additives can be added to the hard coat composition to improve its physical properties, such as fluorine-based additives or silicone-based additives that can impart antifouling properties and slipperiness, and inorganic particle components that can improve scratch resistance.
[0021] [Light absorbing layer] In the present invention, a light absorbing layer is provided on the hard coat layer. As the material for the light absorbing layer, metals such as gold, silver, copper, nickel, chromium, tin, and palladium and their alloys, metal nitrides such as titanium nitride, zirconium nitride, hafnium nitride, silicon nitride, aluminum nitride, and titanium oxynitride, and metal oxides such as iron oxide, chromium oxide, and nickel oxide can be used. Among these, it is preferable to use at least one selected from the group consisting of titanium nitride, titanium oxynitride, zirconium nitride, gold, silver, and copper. By using these, it is possible to realize a low luminous reflectance in a wide wavelength range.
[0022] The light absorbing layer is preferably formed by dry film formation. CVD and PVD are used as dry film formation methods, but PVD is generally used. Vapor deposition and sputtering are generally and widely used PVD methods. Vapor deposition and sputtering equipment are commercially available from many equipment manufacturers, including ULVAC, Synchron, and Optran.
[0023] The thickness of the light absorbing layer is preferably 1 to 40 nm, more preferably 1 to 20 nm, even more preferably 2 to 20 nm, even more preferably 2 to 15 nm, and particularly preferably 3 to 10 nm. If the thickness is too thin, the reflectance reducing effect is low, and if the thickness is too thick, it may cause a significant decrease in transmittance. In the present invention, the method described in the examples described later can be used as a method for measuring the thickness of the light absorbing layer.
[0024] It is also possible to provide an adhesive layer between the light absorbing layer and the hard coat layer. The adhesive layer may be, for example, SiO2, SiO x , SiN x , Al2O3, AlO x , AlN x These adhesion layers are formed by dry deposition, and deposition and sputtering are generally used.
[0025] The thickness of the adhesive layer is preferably 1 to 10 nm, more preferably 2 to 5 nm. If the adhesive layer is too thin, the adhesive effect is low, whereas if it is too thick, the optical performance may be adversely affected.
[0026] [Low refractive index layer] In the present invention, a low refractive index layer is provided on the light absorbing layer. The low refractive index layer in the present invention is obtained by curing a low refractive index resin composition containing an active energy ray curable resin, hollow silica, and a fluorine-based compound with active energy rays. In the present invention, the low refractive index resin composition preferably contains a silicone-based compound and a photopolymerization initiator in addition to the active energy ray curable resin, hollow silica, and fluorine-based compound.
[0027] The active energy ray curable resin can be any compound having a functional group capable of being cured by active energy rays, but it is preferable to use one containing a urethane (meth)acrylate component. The urethane (meth)acrylate includes a polymer of a resin material containing a urethane (meth)acrylate derived from a polyol, an isocyanate, and a (meth)acrylate, and a (meth)acrylate. That is, it is preferable to use a mixture of a urethane (meth)acrylate obtained by a dehydration condensation reaction of three components, a polyol, an isocyanate, and a (meth)acrylate, and a (meth)acrylate.
[0028] Hollow silica is characterized by having air inside and a low refractive index. For example, Suluria (product name) made by JGC Catalysts and Chemicals is commercially available as hollow silica, but is not limited thereto. The hollow silica is preferably mixed in a ratio of active energy ray curable resin / hollow silica=90 / 10 to 10 / 90 (mass%), more preferably 80 / 20 to 20 / 80 (mass%). If the hollow silica content is too high, the scratch resistance decreases, and if it is too low, the refractive index increases and sufficient anti-reflection performance may not be obtained.
[0029] The fluorine-based compound preferably has a perfluoropolyether bond. Although it is possible to use synthetic products of these compounds, it is also possible to easily obtain commercially available products. For example, the Megafac RS series of DIC, the KY series of Shin-Etsu Chemical, and the Optool series of Daikin can be used. The content of the fluorine-based compound in the low refractive index resin composition is preferably from 1 to 30% by mass, and more preferably from 5 to 20% by mass.
[0030] Silicone compounds having polyalkylsiloxane bonds are preferably used. These compounds can be synthetic products, but they can also be easily obtained commercially. For example, Shin-Etsu Silicone's KP series, BYK Japan's BYK series, EVONIK's TEGO Glide series, etc. can be used.
[0031] The fluorine-based compound and the silicone-based compound may be used in combination.
[0032] The low refractive index resin composition is preferably curable with active energy rays, more preferably with ultraviolet rays, and therefore preferably contains a photopolymerization initiator. As the photopolymerization initiator, Omnirad 184 (formerly IRGACURE 184) (1-hydroxy-cyclohexyl-phenyl-ketone) manufactured by IGM Resins BV, Omnirad 1173 (formerly IRGACURE 1173) (2-hydroxy-2-methyl-1-phenyl-propan-1-one), Omnirad TPO H (formerly IRGACURE TPO) (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide), Omnirad 819 (formerly IRGACURE 819) (bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide), EsacureONE (oligo(2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone) manufactured by Lamberti, and the like are preferably used.
[0033] The mixture of active energy ray curable resin, hollow silica, and fluorine-based compound (further, silicone-based compound and photopolymerization initiator, which are preferably added) is generally used by diluting with organic solvent.As the organic solvent, for example, toluene, xylene, ethyl acetate, propyl acetate, butyl acetate, methyl cellosolve, ethyl cellosolve, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, methyl alcohol, ethyl alcohol, isopropyl alcohol, butyl alcohol, diacetone alcohol, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, hexane, heptane, octane, decane, dodecane, propylene glycol monomethyl ether, 3-methoxybutanol, etc. can be mentioned. The organic solvent is preferably used so that the solid content in the low refractive index resin composition is 0.5 to 10 mass %, more preferably 1 to 5 mass %. If the amount of the organic solvent used is too large, it becomes difficult to control the film thickness, and if the amount is too small, it may cause deterioration of the appearance.
[0034] For example, a low refractive index layer can be formed by diluting a mixture of active energy ray curable resin, hollow silica, a fluorine-based compound, and a photopolymerization initiator with an organic solvent, coating the mixture by a predetermined method, drying the organic solvent, and curing the mixture with active energy rays. During the process of drying the organic solvent, the fluorine-based compound, which has a low surface free energy, appears on the surface, making it possible to achieve anti-soiling function without forming an anti-soiling layer.
[0035] Coating can be performed by a common method, such as a bar coater, a spin coater, a gravure coater, a comma coater, or a die coater.
[0036] A low refractive index layer can be obtained by diluting a low refractive index resin composition with an organic solvent, coating, drying, and curing with active energy rays. Examples of active energy rays include ultraviolet rays, near-ultraviolet rays, and visible rays, with ultraviolet rays being the most commonly used.
[0037] The refractive index of the low refractive index layer at 550 nm is preferably 1.45 or less, more preferably 1.42 or less, and even more preferably 1.40 or less. The lower the refractive index, the better the antireflection performance. In addition, the lower the refractive index, the thinner the light absorbing layer can be, and therefore the better the transmittance. In the present invention, the method for measuring the refractive index can be the method described in the examples described below.
[0038] The antireflection substrate of the present invention preferably has a luminous reflectance of 1.0% or less, more preferably 0.9% or less, and particularly preferably 0.8% or less. A luminous reflectance of 1.0% or less is preferable because it has a good effect of improving visibility. In the present invention, the luminous reflectance can be measured by the method described in the examples described later.
[0039] The anti-reflection substrate of the present invention preferably has a transmittance of 50% or more, more preferably 70% or more. The transmittance in the above range is preferable because it provides a good appearance. In the present invention, the transmittance can be measured by the method described in the examples described later. EXAMPLES
[0040] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to the following examples, and can be modified as desired without departing from the gist of the present invention.
[0041] <Reflectance (luminous reflectance)> The measurements were performed using SD6000 manufactured by Nippon Denshoku Industries Co., Ltd. in accordance with JIS Z 8722-2009. In order to prevent reflection from the back side (substrate layer side) of the film of each example, the surface opposite to the coated surface was treated with black spray, and the reflectance was measured. Specifically, the reflectance was measured using the SCI method, which measures both regular reflected light and diffuse reflected light under a light source of D65, which is a standard light source defined by the International Commission on Illumination (CIE). Using the reflectance measured in this way, the luminous reflectance, which is the stimulus value Y of reflection specified in JIS Z8701, was calculated.
[0042] <Transmittance> The transmittance of light with a wavelength of 550 nm was measured using a spectrophotometer U-4100 manufactured by Hitachi High-Tech Science Corporation.
[0043] <Fingerprint wiping test> 2 μl of oleic acid was dropped onto the test piece as artificial fingerprint fluid, and after spreading it with a silicon pad, a cloth was attached and passed over the artificial fingerprint fluid completely. This procedure was repeated, and those that could be wiped off in 5 times or less were rated as ◯, and those that took 6 times or more were rated as ×.
[0044] <Haze> The haze (%) was measured in accordance with JIS-K-7136 using a haze meter (product name: HM-150) manufactured by Murakami Color Research Laboratory.
[0045] <Thickness of light absorbing layer> A contact step gauge (DektakXT manufactured by Bruker) was used to measure the thickness of the light absorbing layer. A partially masked glass substrate was mounted for each deposition of the light absorbing layer, and the step between the masked undeposited portion and the deposited portion was measured, and the value was taken as the film thickness. When measuring the film thickness of the light absorbing layer on an anti-reflection substrate after deposition in multiple layers, a method of measuring the film thickness by observing the cross section of the film processed by focused ion beam with a transmission electron microscope can be adopted.
[0046] In Examples 1 to 5 and Comparative Examples 1 to 3, a hard coat film (product name: MRF08U (manufactured by Mitsubishi Gas Chemical Co., Ltd.)) was used as the substrate, in which a urethane acrylate-based hard coat composition (B-1) described below was used on the PMMA side of a two-layer film of polycarbonate (PC) and polymethyl methacrylate (PMMA). In Example 6, a hard coat film was used in which a film made of polyethylene terephthalate (PET) (product name: Cosmoshine A4100 (manufactured by Toyobo Co., Ltd.), thickness: 188 μm) was subjected to a urethane acrylate-based hard coat treatment in the same manner as above, and in Example 7, a hard coat film was used in which a film made of triacetyl cellulose (TAC) (product name: TD80UL (manufactured by Fujifilm Co., Ltd.), thickness: 80 μm) was subjected to a urethane acrylate-based hard coat treatment in the same manner as above.
[0047] Low refractive index resin composition (A-1) To form the low refractive index layer, a curable low refractive index coating was prepared as follows. First, dry air was introduced into a five-neck flask equipped with a stirrer, a thermometer, a cooler, a monomer dropping funnel, and a dry air inlet tube to dry the inside of the system. Then, 58.9 parts by mass of 2,2,3,3-tetrafluoro-1,4-butanediol (C4DIOL manufactured by Exfluor Research Corporation), 279.8 parts by mass of pentaerythritol triacrylate, 0.5 parts by mass of dibutyltin laurate as a polymerization catalyst, and 500 parts by mass of methyl ethyl ketone as a solvent were added to the five-neck flask and heated to 60°C. Then, 161.3 parts by mass of isophorone diisocyanate were added and reacted at 60 to 70°C. It was confirmed by infrared absorption spectroscopy that the isocyanate residue in the reactant had been consumed, and the reaction was terminated to obtain a hexafunctional urethane acrylate oligomer. Furthermore, 2-(2-vinyloxyethoxy)ethyl acrylate (VEEA) was mixed with the urethane acrylate oligomer (urethane acrylate liquid) at a ratio of urethane acrylate liquid / VEEA=90 / 10 (mass %). Hollow silica (Sururia 4320 manufactured by JGC Catalysts and Chemicals) was added to the liquid component of the resin material thus obtained, and mixed so that the ratio of resin material / hollow silica was 50 / 50 (mass%) in terms of solid content. Furthermore, 5 mass% of 1-hydroxy-cyclohexyl-phenyl-ketone (I-184 manufactured by BASF) as a photopolymerization initiator, 10 mass% of Megafac RS-90 (manufactured by DIC: solid content is 10 mass% and diluted with solvent MEK), which is a fluorine-based compound, and 10 mass% of BYK-UV3575 (modified polydimethylsiloxane-based surfactant manufactured by BYK-Chemie) were added to the low refractive coating material raw material thus obtained (resin material + hollow silica) and dissolved, and a solvent (propylene glycol monomethyl ether) was added to adjust the concentration so that the solid content was 1.5 mass%. The amount of each additive is shown as mass % relative to 100% solid content of the low refractive coating material, where the solid content of the low refractive coating material is taken as 100% by mass.
[0048] Hard Coat Composition (B-1) The hard coat paint was prepared by adding urethane acrylate UN-954 (manufactured by Negami Chemical Industries Co., Ltd.), 5% by mass of 1-hydroxy-cyclohexyl-phenyl-ketone (I-184 manufactured by BASF) as a photoinitiator, 1% by mass of BYK-3550 (manufactured by BYK Japan Co., Ltd.) as a leveling agent, and a solvent (propylene glycol monomethyl ether) to adjust the concentration to 30% by mass of solids. The amount of each additive was described in mass % relative to 100% by mass of the solids content of the hard coat paint, assuming that the solids content of the hard coat paint is 100% by mass.
[0049] The low refractive index resin composition (A-1) was applied to a glass plate and dried at 100°C for 2 minutes, with an integrated light dose of 400 mJ / cm 2 The coating was cured with UV light at 550 nm to form a low refractive index layer. The refractive index of the low refractive index layer was measured with a spectroscopic ellipsometer (Horiba, Ltd. Auto SE) and found to be 1.38. The refractive index of the hard coat composition (B-1) was measured in the same manner as above and found to be 1.50.
[0050] Example 1 On the hard-coated surface of the above-mentioned substrate (product name: MRF08U), copper was sputtered to form a film having a thickness of 3.0 nm to form a light-absorbing layer. Next, the low refractive index resin composition (A-1) was coated on the light-absorbing layer with a bar coater so that the film thickness after drying and UV curing was 100 nm, and after drying at 100°C for 2 minutes, it was applied with an integrated light dose of 400 mJ / cm. 2 A low refractive index layer was formed by UV curing, and an anti-reflection substrate was produced. The luminous reflectance and transmittance of the obtained anti-reflection substrate were measured, and the luminous reflectance was 0.60% and the transmittance was 87%. A fingerprint wiping test was performed, and the result was ◯.
[0051] Example 2 Titanium nitride was sputtered onto the hard-coated surface of the above-mentioned substrate (product name: MRF08U) to form a film having a thickness of 6.0 nm, forming a light-absorbing layer. Next, a low refractive index resin composition (A-1) was coated onto the light-absorbing layer using a bar coater so that the film thickness after drying and UV curing was 100 nm, and after drying at 100°C for 2 minutes, an integrated light dose of 400 mJ / cm was applied. 2 A low refractive index layer was formed by UV curing, and an anti-reflection substrate was produced. The luminous reflectance and transmittance of the obtained anti-reflection substrate were measured, and the luminous reflectance was 0.75% and the transmittance was 80%. A fingerprint wiping test was performed, and the result was ◯.
[0052] Example 3 On the hard-coated surface of the above-mentioned substrate (product name: MRF08U), titanium nitride was sputtered to form a film having a thickness of 3.6 nm to form a light-absorbing layer. Next, the low refractive index resin composition (A-1) was coated on the light-absorbing layer with a bar coater so that the film thickness after drying and UV curing was 85 nm, and after drying at 100°C for 2 minutes, it was applied with an integrated light dose of 400 mJ / cm. 2 A low refractive index layer was formed by UV curing, and an anti-reflection substrate was produced. The luminous reflectance and transmittance of the obtained anti-reflection substrate were measured, and the luminous reflectance was 0.49% and the transmittance was 85.6%. A fingerprint wiping test was performed, and the result was ◯.
[0053] Example 4 Titanium nitride was sputtered onto the hard-coated surface of the above-mentioned substrate (product name: MRF08U) to form a film with a thickness of 6.4 nm to form a light-absorbing layer. Next, a low refractive index resin composition (A-1) was coated onto the light-absorbing layer with a bar coater so that the film thickness after drying and UV curing was 85 nm, and after drying at 100°C for 2 minutes, an integrated light dose of 400 mJ / cm was applied. 2 A low refractive index layer was formed by UV curing, and an anti-reflection substrate was produced. The luminous reflectance and transmittance of the obtained anti-reflection substrate were measured, and the luminous reflectance was 0.50% and the transmittance was 82.2%. A fingerprint wiping test was performed, and the result was ◯.
[0054] Example 5 Titanium nitride was sputtered onto the hard-coated surface of the above-mentioned substrate (product name: MRF08U) to form a film with a thickness of 11.3 nm to form a light-absorbing layer. Next, a low refractive index resin composition (A-1) was coated onto the light-absorbing layer with a bar coater so that the film thickness after drying and UV curing was 85 nm, and after drying at 100°C for 2 minutes, an integrated light dose of 400 mJ / cm was applied. 2 A low refractive index layer was formed by UV curing at 40° C. to prepare an anti-reflective substrate. The luminous reflectance and transmittance of the obtained anti-reflective substrate were measured, and the luminous reflectance was 0.50% and the transmittance was 73.2%. A fingerprint wiping test was performed, and the result was ◯.
[0055] Example 6 Titanium nitride was sputtered onto the hard-coated surface of the above-mentioned PET substrate (product name: Cosmoshine A4100) to form a film with a thickness of 6.4 nm to form a light-absorbing layer. Next, a low refractive index resin composition (A-1) was coated onto the light-absorbing layer with a bar coater so that the film thickness after drying and UV curing was 85 nm, and after drying at 100°C for 2 minutes, an integrated light dose of 400 mJ / cm was applied. 2A low refractive index layer was formed by UV curing, and an anti-reflection substrate was produced. The luminous reflectance and transmittance of the obtained anti-reflection substrate were measured, and the luminous reflectance was 0.58% and the transmittance was 82.1%. A fingerprint wiping test was performed, and the result was ◯.
[0056] Example 7 Titanium nitride was sputtered onto the hard-coated surface of the above-mentioned TAC substrate (product name: TD80UL) to form a film with a thickness of 6.4 nm to form a light-absorbing layer. Next, a low refractive index resin composition (A-1) was coated onto the light-absorbing layer with a bar coater so that the film thickness after drying and UV curing was 85 nm, and after drying at 100°C for 2 minutes, an integrated light dose of 400 mJ / cm was applied. 2 A low refractive index layer was formed by UV curing, and an anti-reflection substrate was produced. The luminous reflectance and transmittance of the obtained anti-reflection substrate were measured, and the luminous reflectance was 0.40% and the transmittance was 82.3%. A fingerprint wiping test was performed, and the result was ◯.
[0057] Comparative Example 1 On the hard-coated surface of the above-mentioned substrate (product name: MRF08U), copper was sputtered to form a film of 4.0 nm thickness to form a light-absorbing layer. Then, SiO2 was sputtered to form a film of 58 nm thickness on the light-absorbing layer to produce an anti-reflective substrate. The luminous reflectance and transmittance of the obtained anti-reflective substrate were measured, and the luminous reflectance was 0.80% and the transmittance was 80%. A fingerprint wiping test was performed, and the result was ×.
[0058] Comparative Example 2 The hard-coated surface of the above-mentioned substrate (product name: MRF08U) was coated with a low refractive index resin composition (A-1) using a bar coater so that the film thickness after drying and UV curing would be 100 nm. After drying at 100°C for 2 minutes, the coating was applied with an integrated light dose of 400 mJ / cm 2A low refractive index layer was formed by UV curing, and an anti-reflection substrate was produced. The luminous reflectance and transmittance of the obtained anti-reflection substrate were measured, and the luminous reflectance was 1.42% and the transmittance was 93.6%. A fingerprint wiping test was performed, and the result was ◯.
[0059] Comparative Example 3 Titanium nitride was sputtered onto the hard-coated surface of the above-mentioned substrate (product name: MRF08U) to form a film having a thickness of 21.1 nm, forming a light-absorbing layer. Next, the low refractive index resin composition (A-1) was coated onto the light-absorbing layer using a bar coater so that the film thickness after drying and UV curing was 85 nm, and after drying at 100°C for 2 minutes, the film was subjected to an integrated light dose of 400 mJ / cm2. 2 A low refractive index layer was formed by UV curing, and an anti-reflection substrate was produced. The luminous reflectance and transmittance of the obtained anti-reflection substrate were measured, and the luminous reflectance was 14.12% and the transmittance was 42.1%. A fingerprint wiping test was performed, and the result was ◯.
[0060] The results of Examples 1 to 7 and Comparative Examples 1 to 3 are shown in Table 1 below. [Table 1]
Claims
1. An antireflection substrate comprising the following layers (A), (B), (C) and (D) laminated in this order: (A) Base material layer (B) Hard Coat Layer (C) Light absorbing layer (D) A low refractive index layer obtained by curing a low refractive index resin composition containing an active energy ray-curable resin, hollow silica, and a fluorine-based compound with active energy rays. The thickness of the (C) light absorbing layer is 2 to 15 nm, The (C) light absorbing layer is formed by a dry film formation method selected from CVD and PVD, the active energy ray-curable resin in the low refractive index layer (D) contains a urethane (meth)acrylate component, The antireflection substrate as described above, wherein the fluorine-based compound in the (D) low refractive index layer has a perfluoropolyether bond.
2. 2. The antireflection substrate according to claim 1, wherein the light absorbing layer (C) is formed from at least one selected from the group consisting of titanium nitride, titanium oxynitride, zirconium nitride, gold, silver, and copper.
3. 3. The antireflection substrate according to claim 1, wherein the low refractive index layer (D) has a refractive index of 1.45 or less at a wavelength of 550 nm.
4. 4. The antireflection substrate according to claim 1, which has a luminous reflectance of 1.0% or less.
5. The antireflective substrate according to claim 1 , which does not include an antifouling layer.
Citation Information
Patent Citations
Antireflection film
JP1997073001A
Light-absorbing reflection preventing body and its production
JP1998096801A
Electrically conductive antireflection film
JP2002341107A
Antireflection film
JP2005181544A
Antireflection film, optical member, and display device
JP2008070459A